The role of adequate vitamin D levels in the menstrual cycle of reproductive-age women - Ahila Meliana; Hana Salsabila; Bendix Samarta Witarto; Manik Retno Wahyunitisari (Universitas Airlangga, 2022)
HIGHLIGHTS 1. This study reviews the effect of adequate levels of serum vitamin D on menstrual cycle2. Vitamin D affects the length and regularity of menstrual cycle3. Women with vitamin D insufficiency typically report irregular and prolonged menstrual periods than women with adequate vitamin D levels. ABSTRACT Objective: This study investigated the role of adequate vitamin D levels in the menstrual cycle of reproductive-age women. Materials and Methods: We systematically searched using certain key words in PubMed and ScienceDirect for English articles, full articles, published between August 2013 - August 2022 that evaluated the effect of vitamin D levels on the menstrual cycle of women in reproductive age. The results were analyzed qualitatively. Results: Eight studies from 653 recorded articles were eligible for review. Decreased vitamin D levels can cause menstrual cycle irregularities, which are related to a decrease in the hormone estradiol, affecting the menstrual cycle. In addition, lower levels of vitamin D lead to longer menstrual cycles. Conclusion: Vitamin D is vital in the menstrual cycle because it influences the frequency and duration of menstruation.